2021
DOI: 10.1186/s12915-021-01124-y
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer-mediated bacterial strain variation affects host fitness in Drosophila

Abstract: Background How microbes affect host fitness and environmental adaptation has become a fundamental research question in evolutionary biology. To better understand the role of microbial genomic variation for host fitness, we tested for associations of bacterial genomic variation and Drosophila melanogaster offspring number in a microbial Genome Wide Association Study (GWAS). Results We performed a microbial GWAS, leveraging strain variation in the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 112 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…These studies highlight the fact that a single or a small number of host genes are controlling or are controlled by the intestinal microbiome. Conversely, a small number of microbiome genes can affect the host’s metabolic ( 53 ), fitness ( 54 ), and longevity ( 55 ) phenotypes. For example, structural mutations in the gene related to butyrate transport in Anaerostipes hadrus are strongly associated with a reduction in the host’s metabolic risk ( 53 ), and the intestinal microbiome’s thiamine biosynthesis genes, transferred by horizontal transmission, influence the host’s fitness ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlight the fact that a single or a small number of host genes are controlling or are controlled by the intestinal microbiome. Conversely, a small number of microbiome genes can affect the host’s metabolic ( 53 ), fitness ( 54 ), and longevity ( 55 ) phenotypes. For example, structural mutations in the gene related to butyrate transport in Anaerostipes hadrus are strongly associated with a reduction in the host’s metabolic risk ( 53 ), and the intestinal microbiome’s thiamine biosynthesis genes, transferred by horizontal transmission, influence the host’s fitness ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a small number of microbiome genes can affect the host’s metabolic ( 53 ), fitness ( 54 ), and longevity ( 55 ) phenotypes. For example, structural mutations in the gene related to butyrate transport in Anaerostipes hadrus are strongly associated with a reduction in the host’s metabolic risk ( 53 ), and the intestinal microbiome’s thiamine biosynthesis genes, transferred by horizontal transmission, influence the host’s fitness ( 54 ). Considering these previous studies and our results, it is suggested that the interaction between the host and the microbiome involves widespread influence of one’s genes on the activity of the other.…”
Section: Discussionmentioning
confidence: 99%